1995
DOI: 10.1016/0009-9236(95)90052-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on fluvoxamine pharmacokinetics in humans

Abstract: Smokers had lower serum concentrations of fluvoxamine than nonsmokers after a single oral dose of fluvoxamine. This finding is consistent with a possible role of CYP1A2 in fluvoxamine metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 20 publications
4
60
0
Order By: Relevance
“…This has been shown for haloperidol (Jann et al, 1986) and tacrine (Zevin and Benowitz, 1999). Other examples are: fluvoxamine levels in smokers are 1/3 that of nonsmokers (Spigset et al, 1995), clozapine levels are 1/3 lower for men, 1/5 for women compared with nonsmokers (Haring et al, 1989), and smoker olanzapine levels are 1/5 that of nonsmokers (Carrillo et al, 2003). Clearly cessation of smoking can cause "overdose" toxicity for a patient taking any of these medications and then stops smoking.…”
Section: Polycyclic Hydrocarbons and Drug Metabolism 11mentioning
confidence: 94%
“…This has been shown for haloperidol (Jann et al, 1986) and tacrine (Zevin and Benowitz, 1999). Other examples are: fluvoxamine levels in smokers are 1/3 that of nonsmokers (Spigset et al, 1995), clozapine levels are 1/3 lower for men, 1/5 for women compared with nonsmokers (Haring et al, 1989), and smoker olanzapine levels are 1/5 that of nonsmokers (Carrillo et al, 2003). Clearly cessation of smoking can cause "overdose" toxicity for a patient taking any of these medications and then stops smoking.…”
Section: Polycyclic Hydrocarbons and Drug Metabolism 11mentioning
confidence: 94%
“…Fluvoxamine is oxidated by CYPlA2 and CYP2D6 (Spigset et al 1995;Carrillo et al 1996), and fluvoxamine is a very potent inhibitor of the former enzyme (Skjelbo & Brrasen 1992;Brrasen et al 1993;Rasmussen et al 1995). Accordingly fluvoxamine causes pharmacokinetic interactions with drugs metabolised by CYPlA2, such as theophylline (Sperber 1991;Diot et al 1991), caffeine (Jeppesen et al 1996), imipramine (Spina et al 1992), clomipramine (Bertschy et al 1991) and clozapine (Jerling et al 1994;Hiemke et al 1994).…”
mentioning
confidence: 99%
“…Similarly, it has been reported that smokers had a lower fluvoxamine concentration than non-smokers after a single oral dose (50 mg) in a study of healthy volunteers. 17) Together, these results strongly suggest that smoking has a major impact on the steady-state plasma concentration of fluvoxamine in Japanese patients being treated with the drug. It is well established that smoking increases the activity of CYP1A2.…”
Section: Discussionmentioning
confidence: 81%
“…16) Several studies have shown that the disposition of fluvoxamine is affected by cigarette smoking in human, suggesting a potential role of CYP1A2 in the metabolism of fluvoxamine in addition to CYP2D6. 9,17) However, in an in vitro examination, CYP1A2 was found to be not involved in the metabolism of fluvoxamine to fluvoxamine acid.…”
mentioning
confidence: 96%